A Fuzzy Logic Controller to Increase Fault Ride-Through Capability of Variable Speed Wind Turbines. (20th March 2012) - Mokryani, Geev; Siano, Pierluigi; Piccolo, Antonio; Calderaro, Vito
Abstract : A fuzzy controller for improving Fault Ride-Through (FRT) capability of Variable Speed Wind Turbines (WTs) equipped with Doubly Fed Induction Generator (DFIG) is presented. The controller is designed in order to compensate the voltage at the Point of Common Coupling (PCC) by regulating the reactive and active power generated by WTs. The performances of the controller are evaluated in some case studies considering a different number of wind farms in different locations. Simulations, carried out on a real 37-bus Italian weak distribution system, confirmed that the proposed controller can enhance the FRT capability in many cases.